ANALISIS LAPORAN AKUNTABILITAS KINERJA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN MINAHASA SELATAN - Tambarici, Anita Carolina; Kalangi, Lintje; Afandi, Dhullo (Universitas Sam Ratulangi, 2018)
The government must periodically communicate the achievement of the organization's strategic goals and objectives to stakeholders as outlined in the Government Institutional Performance Accountability Report (LAKIP). However, these efforts do not seem to be fully supported by the institutions and bureaucracy in question. This can be evidenced by the finding of more and more cases that harm the country's finances up to trillions of rupiah. These cases are mostly in the form of Corruption, Collusion and Nepotism (KKN) practices carried out by certain elements in institutions and bureaucracy that are owned by the government. In addition, the problems that are often found in LAKIP are frequent points of realization the budget and its achievements are not aligned where the funds or budget realized in an activity are not clear about the details and details so that LAKIP is often not in line with the Strategic Plan prepared by the government. This study aims to analyze the adequacy of the Performance Accountability Report of Government Agencies (LAKIP) of South Minahasa DPMD. The analysis method used in this study is descriptive method with the Balanced Scorecard approach. LAKIP The Community and Village Empowerment Office of South Minahasa Regency is in accordance with the perspective of the Balanced Scorecard that has been implemented. Performance achievements that have been good and have been accomplished by the South Minahasa District DPMD need to be maintained and developed again.Keywords : Accountability, Perfomance, Report, Balanced Scoredcard, DPMD